Perkawinan Beda Agama Menurut Kitab Suci, Ajaran, dan Hukum Gereja - Eduardus Krisna Pamungkas; R.F. Bhanu Viktorahadi (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
Interfaith marriage is one of the fundamental problems in marriage in the Catholic Church. Interfaith marriages are problematic because the Church sees interfaith marriages as obstacles to marriage. Interfaith marriages bring dangers to faith, especially to the faith of the Catholic side. In addition, there are other difficulties, especially in the family's welfare and children's education. Therefore, the Church does not want interfaith marriages to occur, making such marriages an obstacle. However, encounters with people of different religions bring great potential for interfaith marriages. This situation is unavoidable, so an understanding of interfaith marriages in the view of the Catholic Church needs to be explored so that the faithful and couples who wish to have this marriage are aware of the impacts and risks that will occur when this marriage takes place. Thus, an understanding of interfaith marriages in the light of the Bible, Church’s teachings, and based on juridical views becomes essential as a provision for those who navigate the family ark in different faiths